PENGARUH LABA AKUNTANSI, KOMPONEN ARUS KAS, UKURAN PERUSAHAAN TERHADAP HARGA SAHAM PADA PERUSAHAAN KELOMPOK LQ 45 YANG LISTING DI BURSA EFEK INDONESIA - -, Kadarusman (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
: The purpose of this study was to: (1) To determine whether accounting earnings affect stock prices in the LQ group of 45 companies on the Stock Exchange, (2) To determine whether the total cash flow effect on the companys share price on the Stock Exchange group LQ 45, (3) To determine whether operating cash flow effect on the companys stock price on the Stock Exchange group LQ 45, (4) To determine whether the cash flow effect on investment in the companys stock price on the Stock Exchange group LQ 45, (5) To determine whether the financing cash flows affect the price of shares in group LQ 45 in IDX, (6) To determine whether the size of the company affects the companys stock price on the LQ group 45 in IDX. This study focused on 45 LQ group companies listed in Indonesia Stock Exchange for the period 2009-2011. The sample method based on purposive sampling method.Â  The results accounting earnings, total cash flow, operating cash flow, investment cash flow, cash flow financing, firm size does not significantly affect the stock price. Keywords: accounting income, total cash flow, operating cash flow, investment cash flow, cash flow financing, firm size, stock price.